American Football Players in Preseason Training at Risk of Acute Kidney Injury Without Signs of Rhabdomyolysis. Issue 6 (November 2020) - Divine, Jon G.; Clark, Joseph F.; Colosimo, Angelo J.; Detherage, John P.; Donaworth, Michael A.; Hasselfeld, Kimberly A.; Himmler, Aaron; Rauch, Joseph T.; Mangine, Robert E.
Abstract : Objective: This study was designed to identify changes in blood biomarkers that would indicate excessive muscle breakdown during the initial 10 days of preseason training in collegiate American football players and subsequently increase their risk of acute kidney injury (AKI). Design: Prospective cohort study. Setting: Preseason, heat acclimatization period. Participants: Twenty-five Division I American football players. Intervention: Clinical biomarkers for muscle damage were measured during a preseason training camp. Samples were obtained before camp and approximately 5 and 10 days into camp after completion of heat acclimatization training. Main Outcomes: Creatine kinase, myoglobin, lactate dehydrogenase, and creatinine were measured. Glomerular filtration rate (GFR) was calculated. Urine was collected at each blood draw to qualitatively identify hematuria and red blood cells. Results: A high percentage of athletes had an asymptomatic reduction in kidney function over the 10-day period. Ten of 23 athletes did have a significant, 31.6%, mean reduction in GFR, placing each at risk of AKI according to Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE) classification. The plasma myoglobin for the at risk of AKI group had a mean value 8× above their baseline mean on day 5 and statistically significant mean 13× higher on day 10 than baseline. The not at risk of AKI group did not have significant differences between days 0, 5, and 10. Conclusions: A relatively high percentage of athletes had an asymptomatic reduction in kidney function during the intense preseason training period. 43.4% of athletes in this study had a significant 31.6% mean reduction in GFR over the 10 days. According to RIFLE classification, this placed each athlete "at risk" of AKI.